Trade in Carbon and Carbon Tariffs - Christoph Böhringer; Jan Schneider; Emmanuel Asane-Otoo (Environmental and Resource Economics, 2021)
Carbon-based import tariffs are proposed as a policy measure to reduce carbon leakage and increase the global cost-effectiveness of unilateral CO2 emission pricing. We investigate the case for carbon tariffs. For our assessment, we combine multi-region input–output and computable general equilibrium analyses based on data from the World Input–Output Database for the period 2000–2014. The multi-region input–output analysis confirms that carbon embodied in trade has increased during this period, but trade flows from Non-OECD to OECD countries became less important in relative terms since the 2007–2008 financial crisis. The computable general equilibrium analysis suggests that carbon tariffs' efficacy in combating leakage increases in periods when trade in carbon increases. However, its potential to improve the global-cost effectiveness of unilateral emission pricing remains modest. On the other hand, we find that the potential of carbon tariffs to shift the economic burden of CO2 emission reduction from abating developed regions to non-abating developing regions increases sharply between 2000 and 2007, but declines after the financial crisis.
Keywords: D57; D58; Q58; 330; Embodied carbon; Carbon tariffs; Unilateral climate policy; Computable general equilibrium